Iodine Intake Increases IP-10 Expression in the Serum and Thyroids of Rats with Experimental Autoimmune Thyroiditis - Si-lu Cui; Jun Yu; Liu Shoujun (International Journal of Endocrinology)
Here, we sought to establish an experimental autoimmune thyroiditis rat model induced by bovine thyroglobulin (bTg) injection and to investigate pathological changes and variations in serum interferon-γ-inducible protein of 10 kDa (IP-10) in thyroid tissue following iodine treatment. Four-week-old female Lewis rats (n=135) were randomly divided into normal (NC), thyroglobulin (TG), HI, HI+TG, HII, and HII+TG groups; rats in the NC and TG groups drank only distilled water (iodine concentration: 10 μg/L), rats in the HI and HI+TG groups were given water containing 25.7 mg/L iodine, and rats in the HII and HII+TG groups were given water containing 423.3 mg/L iodine. Rats in the TG, HI+TG, and HII+TG groups were immunized with 0.1 mL bTg (8 mg/mL) in incomplete Freund’s adjuvant once every 2 weeks for 6 weeks. Compared with the NC group, the TG, HI+TG, and HII+TG groups exhibited higher iodine intake and increased thyroid weights with increasing iodine doses (P<0.05). The high iodine intake in the TG group was associated with increased CD4+ T cells and serum IP-10. Thus, high iodine consumption aggravated the inflammatory reaction in the thyroid and mild high iodine consumption increased serum IP-10 levels after induction with bTg.